Fast switching behaviour and dielectric parameters of two chiral ferroelectric mesogens. Issue 10 (8th August 2020) - Nepal, Shantiram; Mondal, Sarmistha; Sinha, Anindita; Das, Banani; Das, Malay Kumar; Dmochowska, Ewelina; Herman, Jakub; Czerwiński, Michal
ABSTRACT: Two chiral ferroelectric reactive mesogens showing paraelectric SmA* and ferroelectric SmC* phase have been explored by means of electro-optical and dielectric measurements. The variations of spontaneous polarisation, relaxation time, effective torsional bulk viscosity, dispersion and polarisation anchoring coefficients with respect to temperature have been reported in the entire mesomorphic range. Additionally, helical pitch, static permittivity, dielectric anisotropy, complex permittivity (both real and imaginary parts) and ACconductivity have been determined as a function of frequency and temperature. Both the reactive mesogens are found to possess negative dielectric anisotropy. Also, the AC conductivity varies with the input frequencies and it is maximum for high frequency of 100 kHz. The results obtained have been discussed in the light of the applicability of these fast switching and negative dielectric anisotropy materials as chiral dopants in ferroelectric and antiferroelectric liquid crystal mixtures. GRAPHICAL ABSTRACT: uf0001